The Role of SMEs in Assessing the Contribution of Entrepreneurship to GDP in the Romanian Business Environment - Dan Armeanu; Nicolae Istudor; Leonard Lache (Amfiteatru Economic Journal, 2015)
Given the negative effects of the economic crisis on the Romanian economy, entrepreneurship represents one of the main pillars of economic recovery and the authorities need to act in support of private entrepreneurship initiative. Even though entrepreneurship does not equate to the small and medium-sized enterprises, there is strong support in literature regarding the importance of SMEs in national economies due to the authorities' potential of intervention and their contribution to gross value added. The fluctuating evolution of the Romanian business environment has led to a high volatility of its contribution to GDP, which is especially true in the case of SMEs due to their lack of technology and capital and difficult access to financing, as well as limited know-how compared to the large companies that control the Romanian market. Successful entrepreneurial initiative leads to sustainable businesses and ensures a smooth transition from business ideas to the creation of value added, thus supporting economic growth and the narrowing of macroeconomic gaps which have been generated during the economic recession. As a distinctive and dynamic component of Romanian entrepreneurship, the SME segment has a significant contribution to GDP. This study aims at assessing the contribution of entrepreneurship, through its SME segment, to Romania's GDP in the main economic sectors and, at the same time, the estimation of output gap at sectoral level, thus filling a gap in entrepreneurship-related domestic literature.
Keywords: L26; 330; entrepreneurship; business environment; small and medium-sized enterprises; real GDP; potential GDP; output gap; production function